2016
DOI: 10.1021/acscatal.6b03196
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Transformation of Hydrazones into Halogenated Azabutadienes, Versatile Building Blocks for Organic Synthesis

Abstract: A one-step copper-catalyzed reaction of aldehyde-derived N-substituted hydrazones with CCl4 resulted in efficient synthesis of 4,4-dichloro-1,2-diazabuta-1,3-dienes. It was proven that this C–C bond-forming cascade reaction operates via an addition of trichloromethyl radical to the CN bond of hydrazone followed by a base-induced elimination of HCl. The reaction was found to be very general, as diverse hydrazones possessing various aromatic groups at N-site, as well as aromatic, aliphatic, and heterocyclic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 56 publications
(15 reference statements)
7
47
0
Order By: Relevance
“…13 C NMR (100.6 MHz, CDCl 3 ): δ = 23.4 [N(‐CH 2 ‐ CH 2 ‐) 2 ], 25.6 [=N + (‐CH 2 ‐ CH 2 ‐) 2 ], 50.8 [N(‐ CH 2 ‐CH 2 ‐) 2 ], 51.9 [=N + (‐ CH 2 ‐CH 2 ‐) 2 ], 114.2, 120.7, 123.1, 128.3, 128.6, 129.0, 132.1, 144.3, 156.6 ppm. All spectroscopic data are in agreement with literature data …”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…13 C NMR (100.6 MHz, CDCl 3 ): δ = 23.4 [N(‐CH 2 ‐ CH 2 ‐) 2 ], 25.6 [=N + (‐CH 2 ‐ CH 2 ‐) 2 ], 50.8 [N(‐ CH 2 ‐CH 2 ‐) 2 ], 51.9 [=N + (‐ CH 2 ‐CH 2 ‐) 2 ], 114.2, 120.7, 123.1, 128.3, 128.6, 129.0, 132.1, 144.3, 156.6 ppm. All spectroscopic data are in agreement with literature data …”
Section: Methodssupporting
confidence: 91%
“…All solvents were dried by standard procedures and freshly distilled before use. Dichloro‐substituted 1,2‐diazabuta‐1,3‐dienes were prepared as reported previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronically and sterically different o-propargyloxybenzaldehydes can be used for this aim. Moreover, the corresponding naphthalene derivative was prepared as well (Schemes 2 and 3) [26]. In a similar manner, a set of dienes 2h-o having different aryl substituents at the nitrogen was prepared from the parent o-propargyloxy-benzaldehyde and substituted aryl hydrazines.…”
Section: Synthesis and Characterization Of Condensed Analoguesmentioning
confidence: 99%
“…These compounds can be prepared using the reaction of carbon tetrachloride witH-N-substituted hydrazones of aldehydes in the presence of CuCl as a catalyst. [26,27] Recently we demonstrated that these compounds are also interesting diazodyes [28,29]. The reaction of 4,4-dichloro-1,2-diazabuta-1,3-dienes with sodium azide has been found to open straightforward access to extremely rare 1,1-bis-azides ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%